2006
DOI: 10.1111/j.1365-2613.2006.00503.x
|View full text |Cite|
|
Sign up to set email alerts
|

Transdifferentiation of pulmonary arteriolar endothelial cells into smooth muscle‐like cells regulated by myocardin involved in hypoxia‐induced pulmonary vascular remodelling

Abstract: Myocardin gene has been identified as a master regulator of smooth muscle cell differentiation. Smooth muscle cells play a critical role in the pathogenesis of hypoxia-induced pulmonary hypertension (PH) and pulmonary vascular remodelling (PVR). The purpose of this study was to investigate the change of myocardin gene expression in the pulmonary vessels of hypoxia-induced PH affected by Sildenafil treatment and the involvement of endothelial cells transdifferentiation into smooth muscle cells in the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 45 publications
4
60
1
Order By: Relevance
“…Wild-type or mutant 3 0 -UTRs of HIF-1a ( 29 We previously observed that prolonged exposure to hypoxia could lead to structural changes in small intrapulmonary arteries in rat lungs. 23 In this study, a time-dependent increase in neomuscularization and a thickening of small intrapulmonary arteries was observed, the neomuscularization was demonstrated by a-SMA immunohistochemical staining (Figure 1a). Muscularization of pulmonary arteries was fully established in the advanced stage of PH.…”
Section: Dual-luciferase Assaysmentioning
confidence: 95%
See 1 more Smart Citation
“…Wild-type or mutant 3 0 -UTRs of HIF-1a ( 29 We previously observed that prolonged exposure to hypoxia could lead to structural changes in small intrapulmonary arteries in rat lungs. 23 In this study, a time-dependent increase in neomuscularization and a thickening of small intrapulmonary arteries was observed, the neomuscularization was demonstrated by a-SMA immunohistochemical staining (Figure 1a). Muscularization of pulmonary arteries was fully established in the advanced stage of PH.…”
Section: Dual-luciferase Assaysmentioning
confidence: 95%
“…were exposed to normobaric hypoxia (FIO 2 of 0.10) in an isobaric hypoxic chamber 23 for 8 h per day for a period of 1, 4, 7, 14, 21 or 30 days (n ¼ 5 each). An oxygen analyzer (XP-3180; New Cosmos Electric, Osaka, Japan) was used to monitor oxygen content in the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the studies described above, there is evidence to suggest that EndMT may occur in many other disease settings, such as chronic pulmonary hypertension (Zhu et al, 2006;Arciniegas et al, 2007), atherosclerosis (Mironov et al, 1995), wound healing (Sarkisov et al, 1988;Lee and Kay, 2006), and in both acute and chronic kidney injury (Zeisberg et al, 2008). These emerging reports have characterised EndMT primarily in terms of marker expression, but have not addressed the precise molecular mechanisms of EndMT in disease.…”
Section: Endothelial-to-mesenchymal Transition In Cardiac Fibrosis Anmentioning
confidence: 99%
“…So we tested the protein and mRNA expression of SUR2B and Kir6.1 in aortic and pulmonary arteries to investigate the possible mechanisms responsible for the regulation of vasorelaxation by H 2 S. H 2 S deficiency has been observed in animal models of systemic and pulmonary hypertension [16][17][18] . It also plays important roles in the pathogenesis of cardiovascular diseases [16][17][18][19][20][21][22][23][24] . The main mechanism for the cardiovascular actions of H 2 S was considered to be the activation of K ATP channels, because H 2 S increased whole-cell K ATP channel currents in rat aortic vascular smooth muscle cells [15] .…”
Section: Wwwchinapharcom Sun Y Et Almentioning
confidence: 99%